Internet Marketing Strategies For Intellectual Property - Lim, Chee Yuen (2008)
This case study is focused on the ever-growing potential of the current online business in this twentieth century. The study will be narrowed down to gain insight knowledge of various internet marketing strategies in marketing intellectual property - e-book, or also known as electronic book. The objective of the case study is to thoroughly study, analyze and discuss the various information marketing technique used to enhance auto-pilot money-making machine using the internet and hence, creating a leverage passive income.